Um estudo sobre o problema alocação de salas aplicado à Ufersa - Pau dos Ferros - Holanda, Iorrane Nobre de (Universidade Federal Rural do Semi-Árido, 2018)
Every six months, higher education institutions face the same problem: that of allocating disciplines to classrooms while respecting certain restrictions. This problem is known as the Classroom Assignment Problem, which consists of allocating pre-arranged classes to classrooms. Usually this process is solved by institutions manually which usually takes a lot of time to complete and often do not guarantee the efficient allocation of spaces. Such situation is that faced by the Federal Rural University of the Semi-Arid, which due to the increasing demand needs to adapt to allocate efficiently the available spaces. In total UFERSA has 260 classes in this period of 2018.1 allocated in 37 rooms, with a capacity ranging from 20 to 80 students. Thus, the objective with this work is to carry out a study on CAP to understand, to search and to evaluate, among some existing meta-heuristics, which one (s) could be applied to the classroom assignment problem of UFERSA Campus Pau dos Ferros, which is currently carried out manually. The systematic review showed that the best method to solve the problem is a hybrid technique involving the best aspects of the simulated Annealing and Tabu Search metaheuristics.
Keywords: Problema de alocação de salas; Meta-heurísticas; Otimização; Classroom Assignment Problem; Metaheuristics; Optimization; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA